How does credit guarantee promote the organized participation of smallholder farmers in agricultural production outsourcing? - Qiao, Mei; Wang, Jing; Wang, Bowen (Frontiers in Sustainable Food Systems, 2025)
The participation of smallholder farmers in agricultural production outsourcing through organizational means is of significant importance for enhancing agricultural production capacity and promoting agricultural modernization. Based on survey data from 648 households in the Guanzhong area of Shaanxi Province, this study analyzes the incentives for smallholder farmers to obtain credit guarantees provided by village collectives and grassroots supply and marketing cooperatives using a Logit model. It employs the Propensity Score Matching method to construct a counterfactual hypothesis, estimating the average treatment effect of credit guarantees on smallholder farmers’ organizational participation in agricultural production outsourcing. The study also uses regression adjustment methods to verify the mechanism through which credit guarantees affect smallholder farmers’ organizational participation in agricultural production outsourcing. The results show that: (1) Apart from the gender, education level, and number of plots of the household head, other characteristics of the household head and family, village, and market characteristics are important factors influencing smallholder farmers’ access to credit guarantees. (2) After obtaining credit guarantees, the participation of smallholder farmers in agricultural production outsourcing through organizational means significantly increases. (3) The pathways through which credit guarantees promote smallholder farmers’ organizational participation in agricultural production outsourcing, in order of contribution rate, are increasing agricultural income, reducing operational risks, and enhancing organizational trust. Therefore, support for village collectives and grassroots supply and marketing cooperatives should be increased, and organizational forms should be promoted to facilitate the integration of smallholder farmers with agricultural modernization.